2015
DOI: 10.1002/jcph.670
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Data of Efficacy, Safety, and Tolerability in a Real-Life Setting of THC/CBD Oromucosal Spray-Treated Multiple Sclerosis Patients

Abstract: Delta-9-tetrahydrocannabinol (THC)/cannabidiol (CBD) oromucosal spray was approved as add-on therapy for spasticity in patients with multiple sclerosis (MS). We show our 40-week postmarketing experience regarding efficacy and safety of THC/CBD spray in an Italian cohort of 102 MS patients. Patients were evaluated using the Expanded Disability Status Scale (EDSS) score, the Numerical Rating Scale (NRS) for spasticity, the Ambulation Index (AI), and Timed 25-Foot Walk (T25-FW) at the beginning of treatment and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 37 publications
2
21
0
1
Order By: Relevance
“…Around 30%-39% of patients in the large registries permanently discontinued THC:CBD throughout the observation periods. 31,33,34 Similar percentages of discontinuation rates were seen in the NIS 3840 with the exception of the MOVE-2 Italy study with only 18.5% of patients who had stopped THC:CBD after 3 months. 35 Reasons stated for discontinuation were consistently either the lack of effectiveness and/or adverse events (AEs).…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…Around 30%-39% of patients in the large registries permanently discontinued THC:CBD throughout the observation periods. 31,33,34 Similar percentages of discontinuation rates were seen in the NIS 3840 with the exception of the MOVE-2 Italy study with only 18.5% of patients who had stopped THC:CBD after 3 months. 35 Reasons stated for discontinuation were consistently either the lack of effectiveness and/or adverse events (AEs).…”
Section: Resultssupporting
confidence: 57%
“…39 Likewise, the T25-FW test performed in another monocentric study significantly improved in comparison to baseline within the first month. 40…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, only the stretch reflex assessment was able to distinguish between responders and non-responders, defining two groups where the number of puffs was significantly different, despite the reduced sample size. The use of an objective instrumental neurophysiological measure is particularly interesting when assessing spasticity since the previous works were limited by subjective and clinical scales providing surrogate endpoints lacking objective and quantitative informations (Collin et al, 2007;Farrar et al, 2008;Flachenecker et al, 2014;Killestein et al, 2002;Paolicelli et al, 2015;Wade et al, 2004Wade et al, , 2010Zajicek et al, 2003). The present study demonstrates that assessment of spasticity with the described stretch reflex procedure is feasible, not particularly time-consuming and well tolerated by the subjects.…”
Section: Discussionmentioning
confidence: 61%
“…The THC:CBD oromucosal spray (USAN name Nabiximols, Trademark Sativex) is an association of delta-9-tetrahydrocannabinol and cannabidiol administered by oral puffs and adsorbed via a transmucosal route, active on CB1 and CB2 cannabinoid receptors. Large studies demonstrated its efficacy in relieving symptoms related to spasticity in MS patients showing no significant benefit from other antispastic drugs (Collin et al, 2007;Flachenecker et al, 2014;Paolicelli et al, 2015;Wade et al, 2010;Zajicek et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…CBD is also a direct agonist of vanilloid pain receptors (transient receptor potential cation channel subfamily V member 1 receptor), which are known to mediate pain perception, inflammation, and body temperature . There are also many studies that have demonstrated the protective function of cannabinoids in acute and chronic inflammatory diseases, although long‐term safety and effects of its use have not been studied …”
Section: Discussionmentioning
confidence: 99%